2019
DOI: 10.2147/cmar.s191330
|View full text |Cite
|
Sign up to set email alerts
|

<p>Low-dose of olanzapine has ameliorating effects on cancer-related anorexia</p>

Abstract: BackgroundOlanzapine (OLZ) has become well-known for its antiemetic effects on chemotherapy-induced nausea and vomiting. However, it remains unclear whether OLZ also has efficacy for treating cancer-related anorexia. This study, therefore, retrospectively examined whether or not OLZ administration affects the food intake in anorexic cancer patients who exhibit neither nausea nor vomiting.MethodsEighty patients prescribed OLZ were extracted from 951 inpatients who consulted with our palliative care team at Chib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…OLZ has been used as a model hydrophobic compound for the development of implantable drug delivery systems. Although OLZ is mainly used for the treatment of psychoses and related disorders, such as schizophrenia (National Health Service (NHS), 2021 ), low-dose OLZ can be a promising treatment for other medical conditions such as cancer-related anorexia (Okamoto et al., 2019 ), anorexia nervosa (Dunican & DelDotto, 2007 ; Leggero et al., 2010 ), or acne excoriée (Gupta & Gupta, 2001 ). Moreover, drug dose can be increased by adding more than one implant formulation, as has been previously reported (Karunakaran et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…OLZ has been used as a model hydrophobic compound for the development of implantable drug delivery systems. Although OLZ is mainly used for the treatment of psychoses and related disorders, such as schizophrenia (National Health Service (NHS), 2021 ), low-dose OLZ can be a promising treatment for other medical conditions such as cancer-related anorexia (Okamoto et al., 2019 ), anorexia nervosa (Dunican & DelDotto, 2007 ; Leggero et al., 2010 ), or acne excoriée (Gupta & Gupta, 2001 ). Moreover, drug dose can be increased by adding more than one implant formulation, as has been previously reported (Karunakaran et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, we chose the dose of 2.5 mg per day on the basis of data that showed that weight gain is achieved even with lower doses. 16…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of olanzapine concluded that while 10 mg/day prophylactic dose is statistically and clinically superior to control CINV, there is paucity of data to support the use of a lower doses (5 mg/day or less) (18). Preliminary studies report olanzapine is also highly effective in treating chronic nausea and vomiting unrelated to chemotherapy (19,20), and may improve appetite and caloric intake in advanced cancer patients (21,22).…”
Section: Discussionmentioning
confidence: 99%